Blind Aircraft Worker, 1943 (United Kingdom, 1943)
1943 1939-1945 "Blind Aircraft Worker, 1943" [HFR0052], 1943 With an increasing numbers of service personnel returning from the war with serious disabilities, the Tomlinson Committee was set up in 1941 to look at their rehabilitation and re-employment. In 1943, the Committee recommended that existing classes in Government Training Centres be expanded and adapted to the needs of disabled workers, sheltered employment organised for more seriously disabled people, a quota scheme introduced to encourage recruitment, and Disablement Resettlement Officers employed within the Ministry of Labour to interview and assess the special needs of disabled workers. In 1944, these recommendations were formalised in the Disabled Persons (Employment) Act.